1994
DOI: 10.1159/000196298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Tobacco Smoke Exposure on the Function of Alveolar Macrophages in Mice

Abstract: We evaluated the effect of chronic tobacco smoke exposure on the function of the alveolar macrophage (AM) in mice. Tumor necrosis factor-α production of the AM triggered by lipopolysaccharides was smaller in smoke-exposed mice as compared to control mice but did not reach statistical significance (27.3 ± 4.0 vs. 34.8 ± 4.9 U/ml). The percentage of AM which did not phago-cytize latex particles in the smoke-exposed mice was significantly larger than that in control mice (33.9 ± 2.3 vs. 20.8 ± 2.1%; p < 0.05). la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Studies in the early 1990s (8)(9)(10) showed that the inhalation of CS led to a transient impairment of alveolar macrophage uptake of latex beads or Candida albicans in mice. Richens and colleagues also found an impaired uptake of apoptotic cells by macrophages upon exposure to CS in vivo (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the early 1990s (8)(9)(10) showed that the inhalation of CS led to a transient impairment of alveolar macrophage uptake of latex beads or Candida albicans in mice. Richens and colleagues also found an impaired uptake of apoptotic cells by macrophages upon exposure to CS in vivo (11).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of alveolar macrophages to engulf apoptotic cells was impaired by smoke inhalation in animal models (11). Reversal of the effects of CS on the ability of macrophages to phagocytose apoptotic cells or microorganisms was delayed in proportion to the chronicity of smoke exposure (10,11).…”
mentioning
confidence: 99%
“…5B). Previous studies showed that the expression of Ia antigen on BAL cells increased during lung inflammation caused by silica, asbestos, or tobacco smoke (Struhar et al, 1989;Hartmann et al, 1984;Higashimoto et al, 1994). It was also reported that BAL cells from lungs inflamed by asthma showed increased expression of B7.1 and B7.2 (Burastero et al, 1999;Agea et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…However, phagocytic capacity was improved in COPD subjects who had ceased smoking (ex-smokers), compared to those who were still smoking [19]. Studies in mice also support this observation in that chronic tobacco exposure of mice has been shown to decrease phagocytic capability of AM as well as LPS-induced TNF-α release, although it increased the Ia antigen expression on AM [21]. The phagocytotic activities of macrophages are triggered by their interaction with extracellular matrix components.…”
Section: Risk Factorsmentioning
confidence: 88%